5E analysis of a novel designed hot water storage header integrated vacuum tube solar water heater - Chopra K.; Tyagi V.V.; Pathak S.K.; Sharma R.K.; Mansor M.; Goel V.; Sari A. (Elsevier Ltd, 2024)
In this study, 5-E analysis of a heat pipe equipped vacuum tube collector system for residential warm water application has been carried out. The issue of overheating in heat pipes and low thermal efficiency is the major key issues associated with heat pipe vacuum tube collector. This design completely removes the problem of overheating. In addition to this copper fins mounting with condensers of heat pipe enhance the heat transmission rate between the condenser & water stored in a manifold. The results of an experimental investigation reveal that thermal and exergy outputs of the proposed system were obtained almost 6374% and 410% respectively. The average energy gain at the end of the days selected for Run-A, B, and C was calculated to be 7505, 6912, and 6619 kJ respectively, whereas the average exergy gain for corresponding runs was found to be 928, 700, and 401 kJ respectively. In addition to this, the proposed system can provide hot water of approximately 125 L, 76 L, and 52 L in temperatures 50 C, 55 C, and 60 C respectively. Concerning to techno-economic investigation, the per liter cost of warm water generation for the proposed & electric geyser was observed to be 0.15 INR/L & 0.47 INR/L respectively. The levelized energy cost, net present worth, and payback time were found to be 5.48 INR/kWh, 55,819 INR, and 4.12 years respectively. The amount of CO2 mitigation by the developed system was found to be 18.76, 17.28, and 16.54 tCO2/lifetime for Run-A, B & C respectively. 2023